Periodontal manifestations in pregnant women at the “Vilma Espín” Maternal Home of the Polyclinic November 30 - Hechavarria Martínez, Bárbara (2021)
Objective: Clinical and epidemiological characterization of pregnant women with periodontal disease at the “Vilma Espín” Maternal Home, from the “30 de Noviembre” Teaching Polyclinic. Materials and methods: A descriptive and cross-sectional study was carried out in 47 pregnant women with periodontal manifestations in the "Vilma Espín Guillote" Maternity Home, belonging to the "30 de Noviembre" Teaching Polyclinic, in the city of Santiago de Cuba, in the period from June to December 2018, with the objective of identifying the periodontal status of pregnant women and characterizing said prioritized group with periodontal disease in terms of clinical and epidemiological characteristics. The Russell Periodontal Index was used to determine the severity of the periodontal disease and the Simplified Green and Vermillion Oral Hygiene Index to specify the degree of oral hygiene. Results: It was obtained that 38.2% of the pregnant women with gingival disease were in the third trimester of pregnancy. Mild gingivitis was the one that predominated with 65.9% also in the third trimester. In 95.7% of the cases it was located. Conclusions: pregnant women with gingival disease predominated in the third trimester of pregnancy. Mild gingivitis was found in a higher percentage. Poor oral hygiene was present in a high number of pregnant women, which increased with the severity of the disease and the low level of schooling.